2000
DOI: 10.1002/(sici)1097-0096(200006)28:5<211::aid-jcu1>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of palpable breast cancer

Abstract: Purpose Because of the increasing use of sonography to rule out cancer in women with palpable breast abnormalities, this study was performed to determine the rate of sonographically occult malignancy in this clinical setting. Methods Women who were recommended for biopsy based on mammographic and/or clinical findings underwent breast sonography. This study retrospectively analyzed the subset of patients with palpable malignant lesions. Lesions were classified as visible or occult on mammography and sonography.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Moreover, the ability to differentiate benign and malignant features of solid masses using ultrasound has improved (12). Several studies have shown the utility of sonography in detecting palpable breast cancer that is obscured by mammographically dense breast tissue, with sensitivities ranging from 94.2% to 100% (13,14). With the evolving role of sonography, it is important to determine its role as an adjunct to mammography in focal breast pain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ability to differentiate benign and malignant features of solid masses using ultrasound has improved (12). Several studies have shown the utility of sonography in detecting palpable breast cancer that is obscured by mammographically dense breast tissue, with sensitivities ranging from 94.2% to 100% (13,14). With the evolving role of sonography, it is important to determine its role as an adjunct to mammography in focal breast pain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, unexpected additional intraductal disease can often not be detected by US. [10,[23][24][25] M A N U S C R I P T…”
Section: Difficulties and Pitfallsmentioning
confidence: 99%
“…With the development of 7.5-MHz to 10-MHz linear-array transducers with excellent nearfield resolution, the role of ultrasound has expanded to include the characterization of the shape, margins, and internal matrix of masses and guidance for needle localization, aspiration, and biopsy. Ultrasound is also highly accurate in identifying palpable malignant breast masses, although no single examination alone should be used to exclude malignancy [8].…”
Section: Summary Of Literature Reviewmentioning
confidence: 99%
“…In one study comparing physical examinations, mammography, and ultrasound, the authors concluded that for palpable masses, physical examination and ultrasound formed the optimal preoperative test combination [8]. Mammography was also necessary to detect occult cancer in the contralateral or ipsilateral breast.…”
Section: Summary Of Literature Reviewmentioning
confidence: 99%